The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10803-015-2569-4
|View full text |Cite
|
Sign up to set email alerts
|

Are Sensory Processing Features Associated with Depressive Symptoms in Boys with an ASD?

Abstract: The association between Sensory Processing Features (SPF) and depressive symptoms was investigated at two levels in 150 young males (6-18 years) with an ASD. First, a significant correlation was found between SPF and total depressive symptom scores. Second, different aspects of SPF significantly predicted different depressive symptom factors, with Low Registration (or sensory hyposensitivity) being the most powerful predictor of depressive symptoms. There were also differences in these associations according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 56 publications
5
17
3
Order By: Relevance
“…Sensory issues were also identified as triggers, and were again corroborated as a predictor of self-injury in our quantitative analysis. That both alexithymia and sensory disturbances are predictive of self-injury in autistic people is consistent with the prevalence of these features in other self-harming populations, and with the relationship that both alexithymia and sensory differences show with internalizing symptoms and/or mental ill-health in autism [41][42][43][44][45][46]. Alexithymia is higher than average in adolescent selfharmers and is a well-known correlate of self-injury in clinical populations [47][48][49].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Sensory issues were also identified as triggers, and were again corroborated as a predictor of self-injury in our quantitative analysis. That both alexithymia and sensory disturbances are predictive of self-injury in autistic people is consistent with the prevalence of these features in other self-harming populations, and with the relationship that both alexithymia and sensory differences show with internalizing symptoms and/or mental ill-health in autism [41][42][43][44][45][46]. Alexithymia is higher than average in adolescent selfharmers and is a well-known correlate of self-injury in clinical populations [47][48][49].…”
supporting
confidence: 62%
“…Additionally, it may be that individuals who use NSSI for sensory stimulation are driven more by the correlates or comorbidities of sensory differences rather than the sensory differences per se. Such correlates, in autism, include sociocommunicative abilities, insistence on sameness, cognitive problems and inattention, adaptive behavior, and as previously mentioned, anxiety and other forms of affective difficulties [41][42][43][44][45]. Notably, impulsivity is an intrapersonal factor associated with sensation-seeking through NSSI [73] and with acquired capability for suicide [74], and has indeed been linked to self-injurious behavior [75] and to suicidal acts [25] in autistic children.…”
Section: Discussionmentioning
confidence: 92%
“…For example, loss of absorption in a special interest [Clarke et al, 1989;Gillberg, 1985], agitation, change in sleep pattern or social withdrawal [Ghaziuddin, 2005], have all been identified as potentially unique signs of depression in those with ASC. Recent research has also shown associations between sensory sensitivity and depressive symptoms in those with ASC [Serafini et al, 2017;Bitsika, Sharpley, & Mills, 2016]. Adults with ASC without co-morbid intellectual disability also frequently report trying to camouflage their symptoms in an attempt to fit into social situations, at great potential cost to their mental health [Lai et al, 2016;Rynkiewicz et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Among children with ADHD, those with sensory sensitivity are more likely to show anxiety than those with ADHD alone or those with TD (Reynolds & Lane, 2009). Conversely, various studies have found that underresponsivity was significantly associated with depressive symptoms in children and adolescents with high functioning autism (Bitsika et al, 2016) and children and adolescents with Asperger's syndrome (Pfeiffer et al, 2005). As children with ASD and ADHD show higher rates of sensory sensitivity and/or anxiety and depression than the general population, it is unclear if the association between such behaviors in these clinical groups is causal.…”
Section: Anxiety and Depressionmentioning
confidence: 97%